Pelaksanaan Perjanjian Pembiayaan Murabahah ntara Nasabah dan Pihak Koperasi Baitul Maal Wa Tamwil Syariah Berdaya Kota Kupang - Muhammad Hafiyyan AL- Ghazali Saleh; Siti Ramlah Usman; Helsina Fransiska Pello (Universitas Sains dan Teknologi Komputer, 2024)
Murabahah is one of the fund distribution products that is quite popular with BMT customers because of its profitable characteristics, easy to implement, and with a light risk factor to be taken into account in the application. The purpose of this writing is to find out the implementation of the murabahah financing agreement between the customer and the Baitul Maal Wa Tamwil Cooperative (BMT) Syariah Berdaya Kupang City, The benefits of this research are theoretical, namely as a reference material and contribution to the thinking of knowledge for academics for further research, Practical benefits, which are useful as a form of contribution of thought and input for interested parties, especially for students of the Faculty of Law, This research method is empirical research. that in the implementation of murabahah financing there are three stages, namely the applicant has fulfilled the requirements as an applicant, then the financing department will collect several files that have been submitted by the customer for handling by the survey team, after all are complete, an analysis will be carried out in the field or against prospective customers who conduct murabahah financing. With this murabaha financing can be used for capital increase where the contract is very efficient and easy to apply to customers.